On the feasibility of improved target coverage without compromising organs at risk using online adaptive stereotactic partial breast irradiation (A‐SPBI). Issue 2 (9th November 2022) - Montalvo, Steven K.; Kim, Nathan; Nwachukwu, Chika; Alluri, Prasanna; Parsons, David; Lin, Mu‐Han; Cai, Bin; Zhuang, Tingliang; Hrycushko, Brian; Chen, Liyuan; Timmerman, Robert; Rahimi, Asal
Abstract: Purpose: Describe an early‐adopting institution's experience with online adaptive radiation for stereotactic partial breast irradiation. Methods and materials: Retrospective review of 22 women treated between May 2021 and March 2022 with adaptive stereotactic partial breast irradiation. A total of 106 of 110 fractions were evaluated for dosimetric changes in target coverage and organ‐at‐risk (OAR) dose. Patient set up with stereotactic wooden frame and adapted per fraction. Treatment and planning times were collected prospectively by radiation therapists. Results: Scheduled PTV30 Gy was <95% in 72.1% and <90% in 38.5% of fractions, and both PTV and CTV coverage were improved significantly after adaption, and 83.7% of fractions were delivered as adapted per physician choice. There was no difference in OAR coverage. Average adaptive treatment planning took 15 min and average time‐on‐couch was 34.4 min. Conclusions: Adaptive stereotactic breast irradiation resulted in improved target coverage with equivalent dosing to OARs in an efficient and tolerated treatment time. Improved target coverage allowed for decreased PTV margins compared to prior trial protocols that may improve acute and late toxicities.